Safety and efficacy of antisense oligonucleotides on triglyceride, apolipoprotein C-III, and other lipid parameters levels in hypertriglyceridemia; a network meta-analysis of randomized controlled trials - Abdelrahman Mahmoud; Kerollos Abdelsayed; Ahmed Almahdy Mohamed; Qasi Najah; Anas Abdulkader; Karim Ali; Shehroze Tabassum; Mohamed Riad Abouzid; Basel Abdelazeem; James D. Mills (Lipids in Health and Disease)
Abstract Background Hypertriglyceridemia is an independent risk factor for cardiovascular diseases. In previous trials, apolipoprotein C-III (APOC3) inhibition through the antisense oligonucleotides volanesorsen, olezarsen, and plozasiran reduced triglyceride levels. However, the three medications’ safety and efficacy have yet to be compared. Methods A network meta-analysis was performed to compare multiple doses of the three medications to each other through the placebo. Randomized controlled trials (RCTs) were retrieved by searching PubMed, EMBASE, Web of Science, SCOPUS, and Cochrane until November 22nd, 2024. The mean difference (MD) and 95% confidence interval (CI) were used for continuous outcomes. The risk ratio (RR) and 95% CI were used for dichotomous outcomes. Results Ten RCTs with a total of 1,129 patients were included. volanesorsen 300 mg once weekly showed the most significant percent reduction in triglyceride levels (MD = -91.0%, 95% CI: (-109.2%; -72.8%); P < 0.01). Only plozasiran once monthly, regardless of the dose, showed a non-significant percent reduction in triglycerides. This finding should be taken cautiously as the data were derived from a phase 1 trial with a small sample size. All the regimens significantly reduced APOC3 levels compared to placebo, with plozasiran 100 mg monthly and volanesorsen 300 mg once weekly showing the most significant reduction (MD range: -92.8% to -88.5%; P < 0.01). None of the treatments showed a statistically significant difference in overall adverse events rate compared to the placebo. Conclusion APOC3 antisense oligonucleotide inhibitors effectively reduced triglyceride and APOC3 levels in hypertriglyceridemia with an acceptable safety profile. However, the results should be interpreted cautiously due to the small sample size. Further research is needed to confirm the beneficial effects of APOC3 inhibitors and show strong evidence of the impact of each regimen.